2005
DOI: 10.1101/gr.3952905
|View full text |Cite
|
Sign up to set email alerts
|

Living with two extremes: Conclusions from the genome sequence of Natronomonas pharaonis

Abstract: Natronomonas pharaonis is an extremely haloalkaliphilic archaeon that was isolated from salt-saturated lakes of pH 11. We sequenced its 2.6-Mb GC-rich chromosome and two plasmids (131 and 23 kb). Genome analysis suggests that it is adapted to cope with severe ammonia and heavy metal deficiencies that arise at high pH values. A high degree of nutritional self-sufficiency was predicted and confirmed by growth in a minimal medium containing leucine but no other amino acids or vitamins. Genes for a complex III ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
191
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 197 publications
(196 citation statements)
references
References 55 publications
(66 reference statements)
2
191
0
2
Order By: Relevance
“…This article is a PNAS Direct Submission. 1 To whom correspondence should be addressed. E-mail: merab.kokaia@med.lu.se.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This article is a PNAS Direct Submission. 1 To whom correspondence should be addressed. E-mail: merab.kokaia@med.lu.se.…”
Section: Resultsmentioning
confidence: 99%
“…epilepsy ͉ hippocampus ͉ NpHR ͉ paroxysmal depolarizing shift (PDS) ͉ stimulation train-induced bursting (STIB) W hen archaebacterium Natronomonas pharaonis, living in hyperosmotic conditions of lake Zug in the Sahara desert, is exposed to light, its inward-directed halorhodopsin chloride pump (NpHR) is ativated to create a life-saving membrane potential, which drives across the membrane protons (and other cations) used for ATP synthesis (1,2). Genetically adapted to be expressed in mammalian brain by viral vectors and optically activated with millisecond precision, the transgene NpHR pumps chloride ions into transduced neurons, hyperpolarizing and preventing them from firing action potentials (3,4).…”
mentioning
confidence: 99%
“…It has been previously suggested that this FGPP synthase has evolved from an ancestral IPP synthase of Desulfurococcales (Tabichana et al, 2000). **bifunctional geranyl/farnesylgeranyl diphosphate synthase (C 20 and C 25 , respectively) described in the Halobacteriales Natronomonas pharaonis (Falb et al, 2005). Table S2.…”
mentioning
confidence: 99%
“…N. pharaonis is an extremely haloalkaliphilic archaeon, living in salt-saturated lakes (15) at pH values around 11 (16) and temperatures of optimal growth in the 318 -323 K range (17,18). Cytoplasmic and external salt concentrations can be assumed to be similar, however, with reversed sodium to potassium ratio (19).…”
mentioning
confidence: 99%